Physical Injury and Somatic Complaints: The Mediating Role of Posttraumatic Stress Symptoms in Young Survivors of a Terror Attack. Issue 3 (27th May 2017) - Bugge, Ingrid; Dyb, Grete; Stensland, Synne Øien; Ekeberg, Øivind; Wentzel‐Larsen, Tore; Diseth, Trond H.
Abstract : Physically injured trauma survivors have particularly high risk for later somatic complaints and posttraumatic stress symptoms (PTSS). However, the potential mediating role of PTSS linking injury to later somatic complaints has been poorly investigated. In this study, survivors ( N = 255) were interviewed longitudinally at 2 timepoints after the terror attack on Utøya Island, Norway, in 2011. Assessments included injury sustained during the attack, PTSS (after 4–5 months), somatic complaints (after 14–15 months), and background factors. Causal mediation analysis was conducted to evaluate the potential mediating role of PTSS in linking injury to somatic complaints comparing 2 groups of injured survivors with noninjured survivors. For the nonhospitalized injured versus the noninjured survivors, the mediated pathway was significant (average causal mediation effect; ACME = 0.09, p = .028, proportion = 55.8%). For the hospitalized versus the noninjured survivors, the mediated pathway was not significant (ACME = 0.04, p = .453, proportion = 11.6%). PTSS may play a significant mediating role in the development of somatic complaints among nonhospitalized injured trauma survivors. Intervening health professionals should be aware of this possible pathway to somatic complaints.